The Influence of Story Telling Technique On Students Speaking Skill - Hassan, Muhammad Hassan; Rosmen, Rosmen Rosmen (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The aims of this study were to examine the impact of storytelling approach on students' speaking proficiency and to determine the extent to which storytelling elicits positive responses in English instruction.   The study utilised a one-group pretest-posttest design.   The data was analysed using a repeated measure t-test, and hypothesis testing was conducted using SPSS version 15.0.   The findings demonstrated that the utilisation of storytelling technique is effective in enhancing the students' oral proficiency, particularly in the areas of fluency, grammar, pronunciation, vocabulary, and comprehensibility.   The average score of pupils in the pretest was 49.13, which increased to 62.86 in the posttest.   Regarding speaking skills, there was an improvement in students' fluency from 9.80 to 12.26 (a gain of 2.46), pronunciation from 10.00 to 12.53 (a gain of 2.53), grammar from 9.86 to 13.00 (a gain of 3.14), vocabulary from 9.60 to 12.40 (a gain of 2.80), and comprehension from 9.86 to 12.66 (a gain of 2.80).   The questionnaires yielded a highly favourable response on the impact of narrative style on students' speaking proficiency.   The use of storytelling technique has been found to have a substantial impact on students' speaking abilities and elicit positive responses.